Nitric oxide and cytokine production by glial cells exposed in vitro to neuropathogenic schistosome Trichobilharzia regenti - Macháček, Tomáš; Panská, Lucie; Dvořáková, Hana; Horák, Petr (Parasites & vectors, 2016)
BACKGROUND: Helminth neuroinfections represent a serious health problem, but host immune mechanisms in the nervous tissue often remain undiscovered. This study aims at in vitro characterization of the response of murine astrocytes and microglia exposed to Trichobilharzia regenti which is a neuropathogenic schistosome migrating through the central nervous system of vertebrate hosts. Trichobilharzia regenti infects birds and mammals in which it may cause severe neuromotor impairment. This study was focused on astrocytes and microglia as these are immunocompetent cells of the nervous tissue and their activation was recently observed in T. regenti-infected mice. RESULTS: Primary astrocytes and microglia were exposed to several stimulants of T. regenti origin. Living schistosomulum-like stages caused increased secretion of IL-6 in astrocyte cultures, but no changes in nitric oxide (NO) production were noticed. Nevertheless, elevated parasite mortality was observed in these cultures. Soluble fraction of the homogenate from schistosomulum-like stages stimulated NO production by both astrocytes and microglia, and IL-6 and TNF-α secretion in astrocyte cultures. Similarly, recombinant cathepsins B1.1 and B2 triggered IL-6 and TNF-α release in astrocyte and microglia cultures, and NO production in astrocyte cultures. Stimulants had no effect on production of anti-inflammatory cytokines IL-10 or TGF-β1. CONCLUSIONS: Both astrocytes and microglia are capable of production of NO and proinflammatory cytokines IL-6 and TNF-α following in vitro exposure to various stimulants of T. regenti origin. Astrocytes might be involved in triggering the tissue inflammation in the early phase of T. regenti infection and are proposed to participate in destruction of migrating schistosomula. However, NO is not the major factor responsible for parasite damage. Both astrocytes and microglia can be responsible for the nervous tissue pathology and maintaining the ongoing inflammation since they are a source of NO and proinflammatory cytokines which are released after exposure to parasite antigens.
Keywords: Nitric Oxide; Anti-inflammatory cytokines; Tumor Necrosis Factor-alpha; Astrocytes; Interleukin-6; oxid dusnatý; Proinflammatory cytokines; Neuroinfection; Trichobilharzia regenti; kultivované buňky; Schistosomatidae; Animals; interleukin-6; zvířata; Microglia; myši; neuroglie; Nitric oxide; TNF-alfa; Cells, Cultured; Cathepsin B; Neuroglia; astrocyty; Mice; Avian schistosome